2022
DOI: 10.1371/journal.pgen.1010192
|View full text |Cite
|
Sign up to set email alerts
|

ENPP1 variants in patients with GACI and PXE expand the clinical and genetic heterogeneity of heritable disorders of ectopic calcification

Abstract: Pseudoxanthoma elasticum (PXE) and generalized arterial calcification of infancy (GACI) are clinically distinct genetic entities of ectopic calcification associated with differentially reduced circulating levels of inorganic pyrophosphate (PPi), a potent endogenous inhibitor of calcification. Variants in ENPP1, the gene mutated in GACI, have not been associated with classic PXE. Here we report the clinical, laboratory, and molecular evaluations of ten GACI and two PXE patients from five and two unrelated famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…As ENPP1 produces PPi, a potent endogenous inhibitor of hydroxyapatite crystal formation, it has been reported that certain ENPP1-deficient patients develop PXE, a disorder characterized by ectopic mineralization of the matrix in the skin, eyes, and cardiovascular system (5,26). Reduced concentration of PPi is important in pathogenesis of both GACI and PXE (26), although it is not evaluated in this case report. To date, there have been no reports of PXE in ARHR2 patients until now (Table 2).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As ENPP1 produces PPi, a potent endogenous inhibitor of hydroxyapatite crystal formation, it has been reported that certain ENPP1-deficient patients develop PXE, a disorder characterized by ectopic mineralization of the matrix in the skin, eyes, and cardiovascular system (5,26). Reduced concentration of PPi is important in pathogenesis of both GACI and PXE (26), although it is not evaluated in this case report. To date, there have been no reports of PXE in ARHR2 patients until now (Table 2).…”
Section: Discussionmentioning
confidence: 88%
“…A radiologic evaluation should be performed before conducting surgery in ARHR2 patients, since careful endotracheal intubation is needed to avoid hyperextension in cervical OPLL (25). As ENPP1 produces PPi, a potent endogenous inhibitor of hydroxyapatite crystal formation, it has been reported that certain ENPP1-deficient patients develop PXE, a disorder characterized by ectopic mineralization of the matrix in the skin, eyes, and cardiovascular system (5,26). Reduced concentration of PPi is important in pathogenesis of both GACI and PXE (26), although it is not evaluated in this case report.…”
Section: Discussionmentioning
confidence: 99%
“…Some GACI survivors with ENPP1 variants develop PXE‐like skin and eye findings (Ferreira, Hackbarth, et al, 2021; Ferreira, Kintzinger, et al, 2021), whereas some adult PXE patients harboring ENPP1 variants do not manifest with vascular phenotypes (Jin et al, 2015; Ralph et al, 2022b). The reduced plasma PPi concentrations of varying degrees are reported to correlate, in general, with the severity of pathologic calcification in several monogenic disorders of pathologic calcification, including ABCC6‐deficient PXE (60%–70% reduction) and ENPP1‐deficient GACI (90‐100% reduction) (Ralph et al, 2022a).…”
Section: Biological Relevancementioning
confidence: 99%
“…Some GACI survivors with ENPP1 variants develop PXE-like skin and eye findings Ferreira, Kintzinger, et al, 2021), whereas some adult PXE patients harboring ENPP1 variants do not manifest with vascular phenotypes (Jin et al, 2015;Ralph et al, 2022b).…”
Section: Pathomechanisms Of Enpp1 Variants In Pxementioning
confidence: 99%
See 1 more Smart Citation